THE TEACHING OF ENGLISH IN WRITING CLASS AT SENIOR HIGH SCHOOL: A MULTIMODAL DISCOURSE ANALYSIS - ANGGI SYARIAH HASIBUAN; MASLATHIF DWI PURNOMO; TIEN RAFIDA (TELL - US JOURNAL, 2025)
This study aims to analyze the use of multimodal resources in teaching English writing at the senior high school level, particularly their contribution to content delivery, student engagement, and lesson sequencing. The research was conducted in class X-2 of a public Madrasah Aliyah in Medan with 35 students, using classroom video recordings as the primary data collection method. Data analysis was carried out through O’Halloran’s as Systemic Functional Multimodal Discourse Analysis (SF-MDA), examining ideational, interpersonal, and textual meanings. The recorded lessons were divided into 40 segments covering the entire teaching sequence and analyzed based on verbal, visual, gestural, spatial, digital, and collective synchrony modes. The findings revealed that verbal and visual modes dominated content delivery, gestural and spatial modes directed students’ attention, and interpersonal engagement was enhanced through praise, humor, motivational prompts, digital interaction, and collective activities. Textual meaning was achieved through the integration of multiple modes, marking transitions, providing scaffolding, and maintaining lesson coherence. These results highlight the strategic implementation of multimodal resources as essential for creating an interactive, inclusive, and effective learning environment, offering practical insights for teachers to optimize English writing instruction at the secondary school level.